E-MENTORING EXPERIENCES OF ADOLESCENTS WITH SPECIAL NEEDS: A PHENOMENOLOGICAL STUDY (Proceedings of International Conference on Special Education, 2017)
In the literature of providing support to individuals with special needs, numerous past studies had focused on the benefits of e-mentoring in facilitating the transition process from high school to postsecondary education and employment among adolescents with special needs. Nevertheless, relatively few researchers have explored the problems that could lead to unsuccessful e-mentoring relationship, where mentors and/or adolescents withdraw from an e-mentoring program prior to completion, what more, to identify possible strategies to overcome the barriers. This paper, which highlights only the problems faced by adolescents with special needs during e-mentoring program, is part of a phenomenological research that seeks to better understand the e-mentoring experiences of adolescents with special needs, with the intentions to explore the problems they faced, to identify the strategies they used and to subsequently understand how they benefitted from the e-mentoring program. Using a sample of ten adolescents with special needs, four mentors and six parents, this qualitativebased study used an in-depth interview, observation and document analysis techniques to uncover the phenomenon of study. Findings showed that adolescents with special needs experienced a number of communication difficulties and technological challenges as they participated in the e-mentoring program, which were primarily caused by factors such as disability characteristics, past experiences with abled people and control from parents and school teachers. In general, the findings of the study confirm that adolescents with special needs experience a number of problems as they participate in the e-mentoring program. These results have overthrown the faulty assumption of “every user is techfriendly”. Indeed, there is a population like adolescents with special needs who need to be accommodated so that they can participate in the e-mentoring program effectively.